2021
DOI: 10.2478/mjhr-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices for Whitefly and Thrips in Mungbean

Abstract: This experiment was conducted at the central farm of Sher-e-Bangla Agricultural University, [23.740 N latitude and 90.350 E longitude] Sher-e-Bangla Nagar, Dhaka, Bangladesh, during the period of March to May, 2014 to study the Whitefly and Thrips pest incidence in mungbean and their management practices BARI Mung-5 was used as the test crop for this experiment. The experiment consists of the following treatments: T1: Nitro 505EC (Chloropyrifos+Cypermethrin) @ 2 ml/L of water at 10 days interval; T2: Casper 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The lowest marginal benefit cost ratio (1.60) was obtained from the mechanical control plot. Alam et al (2021) found that the highest benefit cost ratio (12.81) with Voliam Flexi (Thiamethoxam+Chlorantraniliprole) @ 0.25 ml/L of water at 10 days interval and the lowest (4.16) with Allion 2.5 EC (Lamda-Cyhalothrin) @ 2.0 ml/L of water at 10 days interval. The highest BCR found in the treatment Voliam Flexi, may be due to the minimum pest infestation to the other treatment components and the better yield of this treatment.…”
Section: Economic Analysis Of Different Bio-rational Approachesmentioning
confidence: 97%
See 1 more Smart Citation
“…The lowest marginal benefit cost ratio (1.60) was obtained from the mechanical control plot. Alam et al (2021) found that the highest benefit cost ratio (12.81) with Voliam Flexi (Thiamethoxam+Chlorantraniliprole) @ 0.25 ml/L of water at 10 days interval and the lowest (4.16) with Allion 2.5 EC (Lamda-Cyhalothrin) @ 2.0 ml/L of water at 10 days interval. The highest BCR found in the treatment Voliam Flexi, may be due to the minimum pest infestation to the other treatment components and the better yield of this treatment.…”
Section: Economic Analysis Of Different Bio-rational Approachesmentioning
confidence: 97%
“…However, production of the crop per unit area is very low (931 kg/ha) as compared to other countries of the world (BBS, 2021). It ranks fifth both in acreage and production and contributes 6.5% of the total pulse production in Bangladesh (Alam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Flea beetles (Phyllotreta nigripes) attack cotyledons and leaves of seedlings and young plants and feed on them by making innumerable round holes. The percentage of leaf area damaged by flea beetle on BARI Mung-6 is 11.33% (Islam et al, 2021). Older infested leaves dry up, hampering the plant's growth having reduced number of pods (Hossain, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators (Litsinger et al, 1988;Singh and Singh, 1977;Hossain, 2015;Alam et al, 2021) studied insect control by chemical insecticides against mungbean pests. Ahmad et al (1998) found that the application of dimethoate (0.03%) or monocrotophos (0.04%) at 45 and 60 days after sowing effectively reduced the insect pest complex of mungbean.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as a quality pulse in the country but production per unit area is very low (931 kg/ha) as compared to other countries of the world (BBS, 2021). It ranks fifth both in acreage and production and contributes 6.5% of the total pulse production in Bangladesh (Alam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%